(untitled) (Global Journal of Management and Business Research, 2018)
Purpose of Study: The research study defines the list food items consumed at subsistence marketplace and divide it into two major categories- core and non-core food items. thus, the objective of this study is to identify the impact of marketing-mix elements for core-food items on purchase decision by urban bottom of the pyramid (bop) or subsistence consumers. Design/methodology/approach: The research study reviews the existing marketing- mix elements prevalent in western food market (Product, Price, Place, and Promotion), thereby Pretesting, and a pilot survey of the instrument was administered on the respondents. Finally, a survey of six hundred respondents was conducted in six selected high-density slums of Delhi (Capital of India). Then based on the exploratory factor analysis (EFA), existing scales of marketing-mix was refined for the essential food items. A regression model was generated to define the influence of marketing-mix on the purchase behavior of core-food items at the subsistence marketplace. Findings: Key finding emerged from the study suggests that marketing-mix influence BOP purchase behavior of core food items. Research question summary. Contributions: Given the absence of empirical and quantitative studies in BOP segment, this study marks a stepping stone towards obtaining a generalized marketing-mix model for Core - Food item. This research work suggests an integrated model for successful marketing to this market Practical Implications: For managers, this research indicates a set of guidelines for designing marketing-mix for core food items in a consumer-sensitive manner. Social Implications: Recommendations will lead to embracing a long forgotten market in mainstream, economy and improving the standard of their living by providing meaningful choices. Originality Value: This study makes an original contribution towards the revival of existing western marketing-mix based on the subsistence consumer. Paper type: Empirical Research paper Scope: Mar